Group Exhibition-Six workshops in Sarajevo, Academy of Fine Arts, Sarajevo, Bosnia Herzegovina - Antoniou, Klitsa (My University, 2026)
Six workshops in Sarajevo, Academy of Fine Arts, Sarajevo, Bosnia Herzegovina Organized and Curated by Alessandro Stillo